T211. COMPARISON OF REHOSPITALIZATION RATE IN INDIVIDUALS WITH SCHIZOPHRENIA CHANGED FROM PALIPERIDONE PALMITATE TO ORAL ANTIPSYCHOTICS. (18th May 2020) - Ju Lee, Bong; Huh, Lyang; Ju Lee, Hyun
Abstract: Background: Long-acting antipsychotic therapy (LAT) may help effectively manage individuals with schizophrenia by optimizing adherence, improving treatment response, reducing the risk of relapse, and improving long-term outcomes. LAT has an established role in the maintenance treatment of chronic, poorly adherent, and/or severely ill patients in later stages of schizophrenia. It is not yet known whether the positive effects of these LATs are merely on the control of symptoms and preventing relapse or on changes in insights and attitudes to medications, resulting in changes in disease course. Methods: This retrospective, single-center study was conducted within the Department of Psychiatry at Inje University Haeundae Paik Hospital. To investigate the efficacy of LAT on the disease course, we compared re-hospitalization rate, drug attitude inventory (DAI), and The Positive and Negative Syndrome Scale (PANSS) in individuals with schizophrenia who had treated with once-monthly paliperidone palmitate and then switched to oral antipsychotics. Results: A total of 105 patients changed from oral drugs to LAI. Of these, 31 patients were later changed to oral medication. Of the total LAI patients, 32 patients received less than 5 months a week. Thirteen patients were hospitalized for 6 months before LAI change and 3 patients were re-hospitalized during the maintenance period after LAI change. Three patients who did not have hospitalized for 6 months after the change of oral medication but did not have hospitalized during LAI maintenance period were re-hospitalized after changing to oral medication. Of the 72 patients who maintained the LAI for more than 5 months, 28 patients experienced re-hospitalization during oral medication before LAI, 9 of whom were re-hospitalized during the LAI. All of them kept on LAI. Seven patients who changed to oral medication during maintenance were not hospitalized during the maintenance period, but three patients were hospitalized after changing to oral medication. Of the 92 patients who had never been hospitalized within 6 months before the change of LAI, 14 had re-hospitalized after changing to LAI. However, none of the 92 patients who had never been hospitalized changed to oral medication. Regardless of the length of time, 5 (about 16%) were re-hospitalized in 31 patients who changed from LAI to the oral medication again. Interestingly, the patients were not hospitalized during the LAI period. There were 27 dropouts. Twenty patients (19%) after LAI change and 7 patients (6%) after oral change. There was no statistical difference in DAI and PANSS scores after the change from LAI to oral medication. Discussion: As previously known, the inhibition effect of relapse was evident during the LAI period. There was no change in adherence to medication, attitudes toward treatment, and degree of illness within 6 months. There were 27 dropouts. Twenty patients (19%) after LAI change and seven patients (6%) after oral change. It has been a long time since the onset, and 7 patients have moved to the hospital. Most of these seven patients were considered to be the case of compliance problems. Immediately after the change of oral medication, dropout occurred in 4 patients, and the duration of LAI in these patients was 2–5 months. The lack of statistical difference between DAI and PANSS after changing to oral drug in LAI can be attributed to the short interval of 6 months.